Adverse health effects in Canada geese (Branta canadensis) associated with waste from zinc and lead mines in the tri-state mining district (Kansas, Oklahoma, and Missouri, USA) - van der Merwe, Deon; Carpenter, James W.; Nietfeld, Jerome C.; Miesner, John F. (My University, 2011)
ABSTRACT: Lead and zinc poisoning have been recorded in a variety of bird species, including migrating waterfowl such as Canada Geese (Branta canadensis), at sites contaminated with mine waste from lead and zinc mines in the Tri-State Mining District, Kansas, Oklahoma, and Missouri, USA. The adverse health impacts from mine waste on these birds may, however, be more extensive than is apparent from incidental reports of clinical disease. To characterize health impacts from mine waste on Canada Geese that do not have observable signs of poisoning, four to eight apparently healthy birds per site were collected from four contaminated sites and an uncontaminated reference site, and examined for physical and physiologic evidence of metals poisoning. Tissue concentrations of silver, aluminum, arsenic, barium, cadmium, cobalt, chromium, copper, iron, magnesium, manganese, molybdenum, nickel, lead, selenium, thallium, vanadium, and zinc were determined by inductively coupled plasma mass spectroscopy. Adverse health effects due to lead were characterized by assessing blood -aminolevulinic acid dehydratase (ALAD) enzyme activity. Adverse effects associated with zinc poisoning were determined from histologic examination of pancreas tissues. Elevated tissue lead concentrations and inhibited blood ALAD enzyme activities were consistently found in birds at all contaminated sites. Histopathologic signs of zinc poisoning, including fibrosis and vacuolization, were associated with elevated pancreatic zinc concentrations at one of the study sites. Adverse health effects associated with other analyzed elements, or tissue concentrations indicating potentially toxic exposure levels to these elements, were not observed.
Keywords: Branta canadensis; Canada goose; Lead poisoning; Mine waste; Tri-state mining district; Zinc poisoning